Percepção de reduções em inglês como L2 - Amaury Flávio Silva (2016)
The objective of this thesis was to carry out a study on the effects of reduction phenomena in the English language on the perception of native speakers of Portuguese, learners of English as a foreign language (perception-task subjects). In order to conduct the analysis, the recordings of two interviews of the semi-spontaneous genre, produced by native speakers of the English language (production subjects), were selected. Excerpts from these recordings were selected to produce ten units of analysis which contained listening comprehension exercises to be done by the perception-task subjects. Each unit was composed of an excerpt from the interviews that contained gaps that should be filled out with one or more words by the native speakers of Portuguese. The omitted words that would fill in the gaps embraced the presence of reduction phenomena whose acoustic phonetic features were analyzed with the free software PRAAT, version 5.4.12, and examined according to knowledge on the Articulatory Phonology. The issues related to the perception of reduction phenomena were addressed according to the Perceptual Acquisition Model (PAM). The study revealed that the difficulties in the perception are caused not only by the occurrence of reduction phenomena, but also by the presence of high speech rate in contexts characterized by the incidence of homorganic consonants whether or not resulting in the deletion of a segment; by extra-linguistic factors; by the absence of emphasis; by the presence of reduction phenomena together with prosodic factors; by segments that are not assimilated. This research brings about the need to produce materials that aim at helping Brazilian learners of English improve the perception of reduction phenomena. These materials should encompass spontaneous and semi-spontaneous speech samples. This project was approved by the Research Ethics Committee under no. 48036115.8.0000.5482